Anode process on platinum in CaCl2-CaO-based melt - K. V. Tatarenko; A. V. Suzdaltsev; A. P. Khramov; Yu. P. Zaikov (Chimica Techno Acta, 2014)
Methods potentiostatic polarization and cyclic voltammetry obtained new data on the mechanism and kinetics of anodic processes on platinum in the molten CaCl2-KCl-CaO when 725–775 °C. Given thermodynamic values of potential difference probable total reactions in the range of the studied temperature. Using potentiostatic polarization and cyclic voltammetry obtained new data on the mechanism and kinetics of anodic process on platinum in the molten CaCl2-KCl-CaO when 725–775 °C thermodynamic assessment of the probability of occurrence total reactions during electrolysis melt on the basis of CaCl2-CaO using non-carbon anode. It is shown that at high current densities anodic process takes place mainly in the conditions of slow diffusion of electrically active particles to the anode, and at low densities (up to 10 mA/cm2) to their discharge to the atomic and lecular oxygen is preceded by a stage, which can be associated with adsorption of atoms of oxygen or with the formation of an oxide film on the surface of platinum. To detect the nature of this stage, further research is needed.